2002
DOI: 10.1002/nrc.10020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrobenzylthioinosine on adenosine levels and neuronal injury in rat forebrain ischemia

Abstract: SummaryNitrobenzylthioinosine (NBMPR) can potentiate the actions of adenosine through inhibition of adenosine influx mediated by the equilibrative nucleoside transporter subtype 1 (ENTl). As adenosine can decrease ischemic neuronal injury, we tested the hypothesis that peripheral administration of the pro-drug NBMPR-phosphate (NBMPR-P) can increase brain adenosine levels and reduce ischemia-induced loss of hippocampal CA1 neurons. Pre-ischemic, but not post-ischemic, peripheral administration of NBMPR-P signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…However, a recent study using cocultures of astrocytes and neurons [124] suggests that the extracellular pathway can predominate when both cell types are present. This was also indicated by our previous in vivo stroke studies, which demonstrated a neuroprotective effect of the ENT1 inhibitor prodrug NBMPR 5'-phosphate (NBMPR-P) [87,130,133]. We suggested that the active form of this drug inhibited adenosine release from neurons, and inhibited adenosine uptake into astrocytes.…”
Section: Cerebral Ischemiasupporting
confidence: 62%
“…However, a recent study using cocultures of astrocytes and neurons [124] suggests that the extracellular pathway can predominate when both cell types are present. This was also indicated by our previous in vivo stroke studies, which demonstrated a neuroprotective effect of the ENT1 inhibitor prodrug NBMPR 5'-phosphate (NBMPR-P) [87,130,133]. We suggested that the active form of this drug inhibited adenosine release from neurons, and inhibited adenosine uptake into astrocytes.…”
Section: Cerebral Ischemiasupporting
confidence: 62%
“…The beneficial effects of administering the ENT inhibitor dipyridamole during percutaneous transluminal coronary angioplasty in humans are likely to have a similar origin [32]. Transport inhibitors are also potentially of value in the context of ischaemic neuronal injury: pre-ischaemic administration of the pro-drug NBMPR-phosphate has been shown to increase brain adenosine levels and reduce ischaemia-induced loss of hippocampal CA1 neurons in the rat [33]. ENT4 expression is abundant in heart and adenosine transport pH-dependency suggests a contribution to the regulation of extracellular adenosine concentrations during myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of administering the ENT inhibitor dipyridamole during percutaneous transluminal coronary angioplasty in humans are likely to have a similar origin [29]. Transport inhibitors are also potentially of value in the context of ischaemic neuronal injury: pre-ischaemic administration of the pro-drug NBMPRphosphate has been shown to increase brain adenosine levels and reduce ischaemia-induced loss of hippocampal CA1 neurons in the rat [55].…”
Section: Pharmacology and Therapeutic Applicationsmentioning
confidence: 98%